Vocabulary building strategy training for grade school teachers effects on their expressive vocabulary - Gonzales, Sarah B.; Baetiong, Lourdes R.; Metila, Romylyn A.; Vargas, Ma. Lourdes J. (Quezon City College of Education, University of the Philippines Diliman, 2019)
This study aimed to enhance the expressive vocabulary of public grade school teachers through an 18-hour Vocabulary Building Strategy (VBS) training program.
Thesis
Includes bibliographical references (pages 143-161).
Keywords: Vocabulary -- Study and teaching (Elementary) -- Philippines; Elementary school teachers -- In-serve training -- Philippines